Human metabolites of brevetoxin PbTx-2: Identification and confirmation of structure - Guo, Fujiang (2010)
Four metabolites were identified upon incubation of brevetoxin (PbTx-2) with human liver microsomes. Chemical transformation of PbTx-2 confirmed the structures of three known metabolites BTX-B5, PbTx-9 and 41, 43-dihydro-BTX-B5 and a previously unknown metabolite, 41, 43-dihydro-PbTx-2. These metabolites were also observed upon incubation of PbTx-2 with nine human recombinant cytochrome P450s (1A1, 1A2, 2C8, 2C9, 2C19, 2D6, 2E1, 3A4 and 3A5). Cytochrome P450 3A4 produced oxidized metabolites while other CYPs generated the reduced products.